2007
DOI: 10.1590/s0103-50532007000700018
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-mediated and customery synthesis of N-benzoyl- or N-substituted benzoyl-N,N'-dialkylureas from arylcarboxylic acids and N,N'-disubstituted carbodiimides under solvent-free conditions

Abstract: bons rendimentos em condições livre de solvente. Primeiramente, a reação entre um ácido carboxílico e uma carbodiimida dissubstituída foi feita empregando radiação de microondas, e depois a mesma reação foi realizada sob aquecimento convencional. Os rendimentos são comparáveis em ambos os casos.An easy, efficient and quick synthesis of N-benzoyl-(and N-substituted benzoyl)-N,N′-dialkylureas, in good yields, under solvent-free conditions is described. First, the reaction between a carboxylic acid and a disubsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Intermediate 7 was converted into amine 8 under acidic conditions, and coupled directly to N , N -dimethylanthranilic acid ( 9 ). It was already reported that carbodiimide-mediated couplings involving aromatic carboxylic acids such as 9 can result in the formation of N -acylurea adducts through competitive N–O rearrangement [1819]. In order to overcome this problem the mixed-carbonate method was used [20].…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate 7 was converted into amine 8 under acidic conditions, and coupled directly to N , N -dimethylanthranilic acid ( 9 ). It was already reported that carbodiimide-mediated couplings involving aromatic carboxylic acids such as 9 can result in the formation of N -acylurea adducts through competitive N–O rearrangement [1819]. In order to overcome this problem the mixed-carbonate method was used [20].…”
Section: Resultsmentioning
confidence: 99%
“…For the preparation of N-(arenecarbonyl)-N,N 0 -dicyclohexylurea derivatives, see: Kaiser et al (2008);Neves Filho et al (2007); Schotman (1991). For the crystal structures of related N-(arenecarbonyl)-N,N 0 -dicyclohexylurea derivatives, see: Ché rioux et al (2002); Cai et al (2009); Dhinaa et al (2010); Orea Flores et al (2006); Gallagher et al (1999); Wang & Zhou (2008); Wu et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…Reactions of arenecarboxylic acids with dicyclohexylcarbodiimide (DCC) in the presence of a catalyst, such as 1-hydroxybenzotriazole, HOBt, produce N-(arenecarbonyl)-N,N′-dicyclohexylureas (Kaiser et al, 2008;Neves Filho et al, 2007;Schotman, 1991). Several crystal structures of N-(arenecarbonyl)-N,N′-dicyclohexylurea derivatives have been reported (Chérioux et al, 2002;Cai et al, 2009;Dhinaa et al, 2010;Orea Flores et al, 2006;Gallagher et al, 1999;Wang et al, 2008;Wu et al, 2006).…”
Section: S1 Commentmentioning
confidence: 99%
“…In 1995, reactions of substituted benzoic acids with N,N ′-dicyclohexylcarbodiimide (DCC) in the presence of [Bu 3 NH][ClO 4 ]/[Bu 3 N] buffer were shown to afford N -acylurea derivatives, and several improved reactions of DCC with carboxylic acids have been reported . Recently, Srivastava reported the reaction of benzoic acid derivatives and N,N ′-disubstituted carbodiimides under solvent-free conditions in a microwave oven in 2007 . As far as we know, there are no examples of the catalytic synthesis of N -acylureas from aldehydes and N,N ′-disubstituted carbodiimides.…”
mentioning
confidence: 99%
“…14 Recently, Srivastava reported the reaction of benzoic acid derivatives and N,N 0 -disubstituted carbodiimides under solvent-free conditions in a microwave oven in 2007. 15 As far as we know, there are no examples of the catalytic synthesis of N-acylureas from aldehydes and N,N 0 -disubstituted carbodiimides. Herein, we present the first report on a highly effective coupling reaction of aldehydes with N,N 0 -disubstituted carbodiimides catalyzed by NHC under aerobic conditions using several N-heterocyclic carbene precursors (Figure 1).…”
mentioning
confidence: 99%